Incorporation of water-in-oil-in-water (W1/O/W2) double emulsion in a set-type yogurt model. (October 2017) - Lalou, Sofia; Kadri, Hani El; Gkatzionis, Konstantinos
Abstract: The effect of W1 /O/W2 emulsion incorporation in set-type yogurt on the acidification process, physicochemical properties, bacterial growth kinetics and structural characteristics was investigated. The W1 /O/W2 emulsion was formed by using a two-step homogenisation process and milk as the W1 and W2 phases, and stability was monitored with optical microscopy and cryo-SEM. Adding the W1 /O/W2 emulsions reduced the acidification rate, viscosity and water retention capacity. Texture (adhesiveness, cohesiveness, hardness, and gumminess) differed in yogurts containing W1 /O/W2 emulsion compared to controls during the acidification process, however, trends became stable during storage. The growth of S. thermophilus during the acidification process of yogurt was reduced in the presence of W1 /O/W2 emulsion while L. bulgaricus trended higher during storage. This study shows that yogurts containing W1 /O/W2 emulsion are feasible subject to processing modification. Graphical abstract: Highlights: First incorporation of W1 /O/W2 emulsion during set-type yogurt acidification The system was proved stable during acidification and storage. Microbial populations were affected by the presence of W1 /O/W2. Milk stabilised the O-W2 interface without the need for nonionic surfactant.